2015
DOI: 10.1016/j.cyto.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation in microRNA expression in peripheral blood mononuclear cells of sepsis patients is associated with immunopathology

Abstract: Sepsis is a major cause of death worldwide. It triggers systemic inflammation, the role of which remains unclear. In the current study, we investigated the induction of microRNA (miRNA) during sepsis and their role in the regulation of inflammation. Patients, on days 1 and 5 following sepsis diagnosis, had reduced T cells but elevated monocytes. Plasma levels of IL-6, IL-8, IL-10 and MCP-1 dramatically increased in sepsis patients on day 1. T cells from sepsis patients differentiated primarily into Th2 cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 53 publications
(52 reference statements)
2
48
1
Order By: Relevance
“…Finally, we examined the effect of increasing miR-145 expression in ASM cells from COPD patients upon IL-6 and CXCL8 release. Although studies have suggested a correlation between miR-145 expression and IL-6 & CXCL8 release [55][56][57][58], we show for the first time that increasing the expression of miR-145 can reduce the levels of IL-6 & CXCL8 release from the COPD ASM cells to levels comparable to that of the nonsmoker ASM cells. miR-145 is proposed to target SMAD3 in systemic sclerosis (SSc) [59], cystic fibrosis [23], cartilage dysfunction [60], nasopharyngeal cancer [61] and in hypertrophic scar fibroblasts (HSFBs) [62], we show here that this may also be the case in ASM cells from patients with COPD.…”
contrasting
confidence: 52%
“…Finally, we examined the effect of increasing miR-145 expression in ASM cells from COPD patients upon IL-6 and CXCL8 release. Although studies have suggested a correlation between miR-145 expression and IL-6 & CXCL8 release [55][56][57][58], we show for the first time that increasing the expression of miR-145 can reduce the levels of IL-6 & CXCL8 release from the COPD ASM cells to levels comparable to that of the nonsmoker ASM cells. miR-145 is proposed to target SMAD3 in systemic sclerosis (SSc) [59], cystic fibrosis [23], cartilage dysfunction [60], nasopharyngeal cancer [61] and in hypertrophic scar fibroblasts (HSFBs) [62], we show here that this may also be the case in ASM cells from patients with COPD.…”
contrasting
confidence: 52%
“…Microarray analyses, next-generation sequencing, and quantitative RT-PCR are important tools in developing biomarkers [1521, 50, 51, 53, 57, 71, 97, 107, 119–131]. To date, candidate regulatory RNAs are limited to miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…While to role of miRNAs has largely been studies in cells, miRNAs can also readily be found in the blood. Furthermore, stress-related disorders such as PTSD and major depression are associated with changes in blood-borne miRNA [47, 48] and intracellular tissue miRNA are changed by stressor exposure [4952]. Because naked circulating miRNAs are degraded quickly in the bloodstream, most blood-borne miRNA are bound to protective proteins, such as high density lipoprotein and argonaute protein [53, 54], or packaged into protective microvesicles, such as exosomes [26, 27].…”
Section: Regulation Of Stress-induced Sterile Inflammation: Mirna Andmentioning
confidence: 99%